Strategi Nafkah Rumah Tangga Petani Padi Lahan Kering di Desa Kragan, Kecamatan Gondangrejo, Karanganyar - Deviani, Marta Amalia; Widiyanto, Widiyanto; Widiyanti, Emi; Rozaqi, Heny (Universitas Muhammadiyah Semarang, 2024)
This research was conducted with the aim of uncovering daily life, the livelihood strategies implemented, and the sustainability of livelihood strategies for the lives of dry land rice farmer households in Kragan Village. This research was conducted using descriptive qualitative methods with a case study approach. The research location was determined purposively in Kragan Village, Gondangrejo District, Karanganyar Regency. Determination of informants was carried out using purposive sampling and snowball sampling. Data validity uses triangulation of sources and techniques. The research results reveal that (1) On-farm households predominantly utilize financial capital in the form of personal capital. On-farm and non-farm households predominantly utilize human capital. On-farm, off-farm and non-farm households predominantly utilize financial capital in the form of loan capital. (2) Based on the livelihood strategy implemented, dry land rice farming households in Kragan Village are classified into 3, namely on-farm farming households, on-farm and non-farm farming households and on-farm, off-farm and non-farm farming households. (3) The livelihood strategies of on-farm farming households include consolidation, while the livelihood strategies of on-farm and non-farm farming households, and on-farm, off-farm and non-farm farming households include survival.